Detection of various fusion genes by one-step RT-PCR and the association with clinicopathological features in 242 cases of soft tissue tumor - Song, Lingxie; Zhang, Ying; Wang, Yuanyuan; Xia, Qingxin; Guo, Dandan; Cao, Jiachen; Xin, Xin; Cheng, Haoyue; Liu, Chunxia; Jia, Xingyuan; Li, Feng (Frontiers in Cell and Developmental Biology, 2023)
Over the past decades, an increasing number of chromosomal translocations have been found in different STSs, which not only have value for clinical diagnosis but also suggest the pathogenesis of STS. Fusion genes can be detected using various techniques, such as: FISH, RT-PCR and NGS. Among these methods, RT-PCR is convenient to detect fusion genes with higher sensitivity and lower cost. In this study, 242 cases of soft tissue tumors were included, which were detected by one-step RT–PCR in multicenter with seven types of tumors: RMS, pPNET, SS, MLPS, ASPS, DFSP and AFST. 18 cases detected by one-step RT–PCR were further tested by FISH. One case with novel fusion gene detected by RNA-sequencing was further validated by one-step RT-PCR. Total positive rate of fusion genes was 60% (133/213) in the 242 samples detected by one-step RT–PCR, in which 29 samples couldn’t be evaluated because of poor RNA quality. The positive rate of PAX3-FOXO1 was 88.6% (31/35) in ARMS, EWSR1-FLI1 63% (17/27) in pPNET, SYT-SSX 95.4% in SS (62/65), ASPSCR1-TFE3 100% in ASPS (10/10), FUS-DDIT3 80% in MLPS (4/5), and COL1A1-PDGFB 66.7% in DFSP (8/12). For clinicopathological parameters, fusion gene status was correlated with age and location in 213 cases. PAX3-FOXO1 fusion gene status was correlated with lymph node metastasis and distant metastasis in RMS. Furthermore, RMS patients with positive PAX3-FOXO1 fusion gene had a significantly shorter overall survival time than patients with negative fusion gene. Among them, FISH result of 18 cases was concordant with that of one-step RT-PCR. As the most common fusion types of AHRR-NCOA2 in one case of AFST were negative by one-step RT-PCR detection, RNA-sequencing was used to determine the fusion genes, and a novel fusion gene PTCH1-PLAG1 was found. Moreover, the fusion gene was confirmed by one-step RT-PCR with new primers. Our study indicates that one-step RT-PCR displays a reliable tool to detect fusion genes with advantage of high accuracy and low cost. Moreover, it is a great tool to identify novel fusion genes. Overall, it provides useful information for molecular pathological diagnosis and improves the diagnosis rate of STSs.